Strategic Site Selection for Bio-LNG Plant in Indonesia: A Multi-Criteria Scoring Method Approach - Oktariani, Edma Nadhif; Yuliusman, Yuliusman (Journal of Materials Exploration and Findings, 2024)
In Indonesia, the energy sector is still predominantly reliant on fossil fuels, with renewable energy, including liquefied biomethane (Bio-LNG), playing a limited role. Nonetheless, Indonesia has significant potential for Bio-LNG development due to its abundant organic waste resources such as Palm Oil Mill Effluent (POME) from palm oil mills. Having approximately 891 Palm Oil Mills in Indonesia and being spread mostly in Sumatra, this study aims to select a strategic location for a Bio-LNG plant that can enhance logistical efficiency and economic viability for the plant. This study uses Multi-Criteria Decision Making (MCDM) methodologies to assess potential sites based on key criteria: Land Availability, Distance to Source of Feedstock, Distance to Customer Locations, Jetty Availability, and Future Business Developments. This study has narrowed down into focusing on provinces with substantial raw material potential, Riau Province, particularly Dumai City and its surroundings, which emerges as a pivotal hub. Secondary data are gathered to conduct a systematic scoring process evaluates and integrates each criterion to generate a comprehensive ranking of potential sites. The selected site for the Bio-LNG plant is Location 1, at the coordinates of 1.662056, 101.707092, Pelintung, Medang Kampai Subdistrict, Dumai City, Riau. Its strategic positioning, proximity to key transportation routes, availability of abundant feedstock, and access to necessary infrastructure make it an ideal choice. This study aims to advance Bio-LNG infrastructure in Indonesia, promoting cleaner energy solutions, and enhanced supply chain efficiency.